2022
DOI: 10.3389/fimmu.2022.851556
|View full text |Cite
|
Sign up to set email alerts
|

PLX5622 Reduces Disease Severity in Lethal CNS Infection by Off-Target Inhibition of Peripheral Inflammatory Monocyte Production

Abstract: PLX5622 is a CSF-1R inhibitor and microglia-depleting reagent, widely used to investigate the biology of this central nervous system (CNS)-resident myeloid population, but the indirect or off-target effects of this agent remain largely unexplored. In a murine model of severe neuroinflammation induced by West Nile virus encephalitis (WNE), we showed PLX5622 efficiently depleted both microglia and a sub-population of border-associated macrophages in the CNS. However, PLX5622 also significantly depleted mature Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 67 publications
7
56
1
Order By: Relevance
“…As reported, the reduction of antigen-presenting cells (APC) in the blood could be observed in the peripheral blood [ 41 ]. In our study, the CSF1R inhibitor had no lethal effect on immature mice and had no significant impact on the weight growth of mice, but it had a substantial effect on the proportion of monocytes and macrophages in the bone marrow, consistent with a previous study [ 42 , 43 ]. After inhibiting microglia by gene knockout, minocycline, and other methods, changes in cytokines could also be observed, and the changes in some cytokines and the degeneration of retinal cells were consistent with what we observed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As reported, the reduction of antigen-presenting cells (APC) in the blood could be observed in the peripheral blood [ 41 ]. In our study, the CSF1R inhibitor had no lethal effect on immature mice and had no significant impact on the weight growth of mice, but it had a substantial effect on the proportion of monocytes and macrophages in the bone marrow, consistent with a previous study [ 42 , 43 ]. After inhibiting microglia by gene knockout, minocycline, and other methods, changes in cytokines could also be observed, and the changes in some cytokines and the degeneration of retinal cells were consistent with what we observed.…”
Section: Discussionsupporting
confidence: 93%
“…A large number of studies have shown that inhibiting the over-activation of immune cells might decelerate or alleviate the progress of the diseases. In a model of neuroinflammation induced by the West Nile virus encephalitis, PLX5622 inhibited the proliferation and lethal recruitment of immune cells into the infected brain, reducing neuroinflammation, and proved that PLX5622 was a potential target in immune cell-mediated diseases [ 43 ]. In our study, the inhibition of activated microglia reduced pathological angiogenesis in the early stage and then rescued the over-apoptosis of photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…8B-C). These include the previously reported CD86- and CD86+ microglial subsets (Spiteri et al, 2022; Spiteri et al, 2021), as well as a distinct population that we have termed myelin-responsive microglia (MRM), prominent in CerS2 ΔO/ΔO but not CerS2 fl/fl mice (Fig. 8B-C).…”
Section: Resultssupporting
confidence: 68%
“…Brains were processed into single cell suspensions for spectral cytometry, as previously described (Spiteri et al, 2022; Spiteri et al, 2021). Briefly, brain cells were isolated using a 30%/80% Percoll gradient after homogenizing tissue on a gentleMACS dissociator (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
“…Future studies should examine microglia subsets and migration patterns during fungal infection to identify the different ways in which these cells contribute towards pathology. Some of the microglia depletion methods used in our study, including the CSF1R inhibitor PLX5622 (Kerkhofs et al, 2020;Spiteri et al, 2022), are reported to have off target effects on border macrophages within the CNS. The role of non-microglia CNS border macrophages in the control and dissemination of C. neoformans is not fully understood, but they have been shown to become heavily infected with the fungus (Kaufman-Francis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%